"The debt is suffocating to be honest": Student loan debt, prospective sensemaking, and the social psychology of precarity in an allopathic medical school - William H. Burr; Judson G. Everitt; James M. Johnson (Elsevier, 2023)
Confronted with soaring medical school costs and intensifying disparities in physician compensation by specialty, medical students are forced to make sense of medical education debt during the nascent stages of their careers in medicine. Few studies, however, have examined exactly how medical students make sense of these constraints or how this process might influence decisions about which specialty to pursue or affect doctors' wellbeing. Leveraging qualitative data collected from current students across all four years of medical education at a Midwestern allopathic medical school, we document how medical students collectively engage in prospective sensemaking about their debt and how it may affect their futures. We find that debt creates a palpable sense of financial precarity for people entering a high-status profession. We frame our analysis within a burgeoning new literature in organizational sociology and the professions known as inhabited institutionalism, which draws attention to the reciprocal relationships between local interaction and sensemaking with wider institutional pressures. We conclude with discussion of the implications our findings have for the supply of physicians across specialties as well as for the wellbeing of physicians across their careers.